2012
DOI: 10.1111/j.1834-7819.2012.01731.x
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for restoration of single implants and use of cross‐pin retained restorations by Australian prosthodontists

Abstract: Background: Implant supported restorations (ISRs) for the single implant may be cement retained or screw retained. Limited scientific evidence exists to support the superiority of a retention type for either implant or prosthetic success. The aim of this study was to assess preferences of Australian prosthodontists when restoring single implants. In particular, clinical practices for cross-pin retained implant supported restorations for a single implant were investigated. Methods: A written questionnaire compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Rangert et al identified the prosthetic screw as the safety component of the implant system, advocating its ease of retrievability. The contemporary implant systems have eliminated or minimised the occlusal, accessory prosthetic screws for single implant rehabilitation, which coincides with a low clinical preference as well in a recent survey, and the abutment screw has become the primary safety feature of the system . However, the retrieval of a fractured abutment screw without damaging the remaining implant components has found to be often cumbersome.…”
Section: Discussionmentioning
confidence: 98%
“…Rangert et al identified the prosthetic screw as the safety component of the implant system, advocating its ease of retrievability. The contemporary implant systems have eliminated or minimised the occlusal, accessory prosthetic screws for single implant rehabilitation, which coincides with a low clinical preference as well in a recent survey, and the abutment screw has become the primary safety feature of the system . However, the retrieval of a fractured abutment screw without damaging the remaining implant components has found to be often cumbersome.…”
Section: Discussionmentioning
confidence: 98%
“…Out of 73 implant crowns, 15 had mechanical complications of which 60% were related to cross‐pin loosening . However, this is a minor issue and may require addition of gasket which is a simple clinical procedure …”
Section: Discussionmentioning
confidence: 99%
“…29 However, this is a minor issue and may require addition of gasket which is a simple clinical procedure. 30 Despite the statistical similarity in survival rates of crowns fabricated on stock and Encode abutments at 1-year of clinical observation,…”
Section: Discussionmentioning
confidence: 99%
“…Meticulous review of the literature shows that attempts have been made to define specific indications for use of one type of retention in lieu of the other 3 . However, distinct schools of thought exist that favor one type of restoration‐to‐fixture retention versus the other 4 . It is not uncommon for groups of clinicians to use solely one type of retention in the majority of their clinical cases rather than attempting to personalize treatment planning 4 …”
mentioning
confidence: 99%
“…However, distinct schools of thought exist that favor one type of restoration‐to‐fixture retention versus the other 4 . It is not uncommon for groups of clinicians to use solely one type of retention in the majority of their clinical cases rather than attempting to personalize treatment planning 4 …”
mentioning
confidence: 99%